Concentrations and fluxes of biogenic volatile organic compounds above a Mediterranean macchia ecosystem in western Italy - Davison, B.; Taipale, R.; Langford, B.; Misztal, P.; Fares, S.; Matteucci, G.; Loreto, F.; Cape, J. N.; Rinne, J.; Hewitt, C. N. (BIOGEOSCIENCES, 2009)
Emission rates and concentrations of biogenic volatile organic compounds (BVOCs) were measured at a Mediterranean coastal site at Castelporziano, approximately 25 km south-west of Rome, between 7 May and 3 June 2007, as part of the ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions. Concentrations and emission rates were measured using the disjunct eddy covariance (DEC) method utilizing three different proton transfer reaction mass spectrometers (PTR-MS) so allowing a comparison between the instruments. The high resolution data from the PTR-MS instruments considerably enhances the original BEMA measurements of the mid 1990s. Depending on the measurement period, the volume mixing ratios were in the range 1.6-3.5 ppbv for methanol, 0.44-1.3 ppbv for acetaldehyde, 0.96-2.1 ppbv for acetone, 0.10-0.14 ppbv for isoprene, and 0.13-0.30 ppbv for monoterpenes. A diurnal cycle in mixing ratios was apparent with daytime maxima for methanol, acetaldehyde, acetone, and isoprene. The fluxes ranged from 370-440 mu g m(-2) h(-1) for methanol, 180-360 mu g m(-2) h(-1) for acetaldehyde, 180-450 mu g m(-2) h(-1) for acetone, 71-290 mu g m(-2) h(-1) for isoprene, and 240-860 mu g m(-2) h(-1) for monoterpenes. From the measured flux data (7 May-3 June) an average basal emission rate for the Macchia vegetation was calculated of 430 mu g m(-2) h(-1) for isoprene and 1100 mu g m(-2) h(-1) for monoterpenes.
APSAPSThe following values have no corresponding Zotero field: pub-location: BAHNHOFSALLEE 1E, GOTTINGEN, 37081, GERMANY publisher: COPERNICUS GESELLSCHAFT MBH
Keywords: BVOCS; Emission rates; Mediterranean; Monoterpenes

Stomatal uptake and stomatal deposition of ozone in isoprene and monoterpene emitting plants - Fares, S.; Loreto, F.; Kleist, E.; Wildt, J. (Plant Biology, 2008)
Volatile isoprenoids were reported to protect plants against ozone. To understand whether this could be the result of a direct scavenging of ozone by these molecules, the stomatal and non-stomatal uptake of ozone was estimated in plants emitting isoprene or monoterpenes. Ozone uptake by holm oak (Quercus ilex, a monoterpene emitter) and black poplar (Populus nigra, an isoprene emitter) was studied in whole plant enclosures (continuously stirred tank reactors, CSTR). The ozone uptake by plants was estimated measuring ozone concentration at the inlet and outlet of the reactors, after correcting for the uptake of the enclosure materials. Destruction of ozone at the cuticle or at the plant stems was found to be negligible compared to the ozone uptake through the stomata. For both plant species, a relationship between stomatal conductance and ozone uptake was found. For the poplar, the measured ozone losses were explained by the uptake of ozone through the stomata only, and ozone destruction by gas phase reactions with isoprene was negligible. For the oak, gas phase reactions of ozone with the monoterpenes emitted by the plants contributed significantly to ozone destruction. This was confirmed by two different experiments showing a) that in cases of high stomatal conductance but under low CO2 concentration, a reduction of monoterpene emission was still associated with reduced O3 uptake; and b) that ozone losses due to the gas phase reactions only can be measured when using the exhaust from a plant chamber to determine the gas phase reactivity in an empty reaction chamber. Monoterpenes can therefore relevantly scavenge ozone at leaf level contributing to protection against ozone.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: isoprene; Monoterpenes; Ozone uptake; photosynthesis; reaction chambers; Stomatal conductance